THE INFLUENCE OF FIRST LANGUAGE ON EFL LEARNERS’ WRITING ERRORS (The Case Study: EFL Iraqi postgraduate students in Malaysia) - Ban AbdulameerAbdulhafud (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The present study is concerned with the effect of 1st language on English writing skills of EFL Iraqi postgraduate students in Malaysia to prove or disprove the postulation; if the student does not make a transfer between the two languages his writing skills will improve. Two types of instruments were used, 1st was a questionnaire, 2nd was an analysis of students’ writing. The analysis of the questionnaire demonstrates that many students have difficulties in English writing. They relate back to L1 to write, which in turn increases their writing mistakes. They believe that their writing contain little, if any, mistakes. However, the analysis of their writing shows errors at different linguistic levels namely syntactic, lexical and semantic levels. The misconception they have is likely due to the fact that they are not adequately proficient in English. The numerous mistakes are related to lack of comprehension. Thus, a decrease in transfer will assist language learners to write with fewer errors. The more linguistic competence they possess, the better their writing become and vice versa